2019
DOI: 10.1128/jvi.00227-19
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex Virus 2 in Autonomic Ganglia: Evidence for Spontaneous Reactivation

Abstract: Herpes simplex virus 2 (HSV-2) can be transmitted in the presence or absence of lesions, allowing efficient spread among the general population. Recurrent HSV genital lesions are thought to arise from reactivated latent virus in sensory cell bodies of the dorsal root ganglia (DRG). However, HSV-2 has also been found latent in autonomic ganglia. Spontaneous reactivation or a low level of chronic infection could theoretically also occur in these peripheral nervous tissues, contributing to the presence of infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 37 publications
0
9
0
1
Order By: Relevance
“…In one study, 24% of patients showed systemic symptoms, such as fever, headaches, and malaise [ 133 ]. Typically, 10–14 days post-exposition, alphaherpesvirus latency is established within the cell body’s nucleus of sensory nerves (e.g., cervical, lumbosacral, or autonomic ganglia) [ 141 ].…”
Section: Human Latent Virus (Hlv) Selection With Common Interests In Czsmentioning
confidence: 99%
See 3 more Smart Citations
“…In one study, 24% of patients showed systemic symptoms, such as fever, headaches, and malaise [ 133 ]. Typically, 10–14 days post-exposition, alphaherpesvirus latency is established within the cell body’s nucleus of sensory nerves (e.g., cervical, lumbosacral, or autonomic ganglia) [ 141 ].…”
Section: Human Latent Virus (Hlv) Selection With Common Interests In Czsmentioning
confidence: 99%
“…Short noncoding RNAs along with long noncoding RNAs (lncRNAs) are LAT transcripts typically involved in the maintenance of latency [ 114 , 142 , 143 ]. Nevertheless, not all infected latency cells express LATs, and some studies support the function of LATs in reactivation or, at least, in establishing a high risk of spontaneous reactivation [ 141 ]. The expression of lytic transcripts in latency is favorable for reactivation events rather than silent states, heightening the susceptibility to triggering factors ( Table 2 ).…”
Section: Human Latent Virus (Hlv) Selection With Common Interests In Czsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional advantages include higher quantification precision, especially at lower target template copy numbers, as well as greater multiplexing ability because of digital PCR's unique amplitude or ratiobased higher order multiplexing [21]. Digital PCR has also been widely used in virus/pathogen analysis [22,23], in addition to cancer mutation detection [24][25][26][27], GMO screening [28], gene and miRNA expression testing, copy number variation (CNV) determination [29][30][31], as well as nucleic acid reference standard and NGS library quantification [32].…”
Section: Introductionmentioning
confidence: 99%